2010
DOI: 10.1038/onc.2010.24
|View full text |Cite
|
Sign up to set email alerts
|

Mutant p53 initiates a feedback loop that involves Egr-1/EGF receptor/ERK in prostate cancer cells

Abstract: Early Growth Response-1 (Egr-1) is overexpressed in human prostate tumors and contributes to cancer progression. On the other hand, mutation of p53 is associated with advanced prostate cancer, as well as with metastasis and hormone independence.This study shows that in prostate cell lines in culture, Egr-1 overexpression correlated with an alteration of p53 activity due to the expression of SV40-TAg or to a mutation in the TP53 gene. In cells containing altered p53 activity, Egr-1 expression was abolished upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 32 publications
5
48
0
Order By: Relevance
“…Egr-1 upregulates the expression of multiple genes, including PTEN and several tumor suppressor genes. Transcription of Egr1 was previously shown to be induced by MAPK pathways, especially by ERK signaling through phosphorylation and activation of Elk1 using MEK inhibitors or the natural anticancer compound curcumin, in various types of tumors (25)(26)(27)(28). In addition to the transcriptional regulation of Egr1 by ERK, we show here that KRT19 plays a role in regulating the nuclear localization of Egr1 by modulating its association with Imp7.…”
Section: Discussionsupporting
confidence: 54%
“…Egr-1 upregulates the expression of multiple genes, including PTEN and several tumor suppressor genes. Transcription of Egr1 was previously shown to be induced by MAPK pathways, especially by ERK signaling through phosphorylation and activation of Elk1 using MEK inhibitors or the natural anticancer compound curcumin, in various types of tumors (25)(26)(27)(28). In addition to the transcriptional regulation of Egr1 by ERK, we show here that KRT19 plays a role in regulating the nuclear localization of Egr1 by modulating its association with Imp7.…”
Section: Discussionsupporting
confidence: 54%
“…Mutant p53 expression correlates with elevated MAPK/ERK pathway activity (ref. 43 and Supplemental Figure 7D) and increased levels of EGR1 transcription factor (44), which modifies expression of several genes involved in cytoskeletal regulation and filopodia formation (45). We observed that inhibition of the MAPK/ERK pathway efficiently reduced EGR1 and Myo10 in p53 mutant MDA-MB-231 cells but not p53 WT MCF10A cells ( Figure 7A).…”
Section: Myo10 Regulates Dissemination Of Breast Cancer Cells In Vivomentioning
confidence: 99%
“…Its involvement has been reported in cancer metastasis [12], inflammation [13], atherosclerosis [14], and ischemic injury [15]. Moreover, recent studies revealed that abnormal expression and function of Egr-1 are linked to animal models of fibrosis, as well as human fibrotic disorders, including idiopathic pulmonary fibrosis and scleroderma [16,17,18].…”
Section: Introductionmentioning
confidence: 99%